Comparative Biometry, habitat structure and distribution of four endemic snakehead (Teleostei: Channidae) species of Assam, India - Goswami, M M; Borthakur, Arunav; Pathak, Janardan (Journal of the Inland Fisheries Society of India, 2016)
Snakeheads of the family Channidae viz Channa barca, C. aurantimaculata, C. stewarti and C. bleheri are of restricted distribution in some areas of Assam. Studies on biometry, habitat and distribution of the four species were carried out. The microhabitat characteristics of all the four species are of burrowing type. The rare and dwindling status of C. barca is of great concern. The declining occurance of the fishin relation to human interference has been discussed. A key to identification of fishes of the Genus Channa of Assam is provided.